Using logarithmic rules, we can simplify this expression:
log2(8) + log2(2) = log2(8 x 2)
Simplifying the expression within the logarithm, we get:
log2(16)
Therefore, log2(8) + log2(2) = log2(16)
Simplify log2(8)+log2(2) into single logarithm
3 answers
since 16=2^4, log2(16) = 4
also, log2(8)+log2(2) = 3+1 = 4
also, log2(8)+log2(2) = 3+1 = 4
Yes, that's correct! We can also simplify the expression using the fact that log2(8) = 3 and log2(2) = 1, and thus:
log2(8) + log2(2) = 3 + 1 = 4
Either way, we get the same result: log2(8) + log2(2) = log2(16) = 4.
log2(8) + log2(2) = 3 + 1 = 4
Either way, we get the same result: log2(8) + log2(2) = log2(16) = 4.